An introduction to English sociolinguistics - Trousdale, Graeme (Edinburgh textbooks on the English language, 2010)
This textbook, aimed primarily at beginning undergraduates studying for degrees in English, provides an introduction to a range of sociolinguistic theories and the insights they provide for a greater understanding of varieties of English, past and present. Drawing on both qualitative and quantitative approaches to sociolinguistic variation, the book provides a systematic overview of such topics as: 'English' as a social and as a linguistic concept; The relationship between regional and social dialectology, and their application to the study of English; English historical sociolinguistics, from.
Keywords: Sociolinguistics; English language : Variation; English language : Social aspects; SOCIAL SCIENCE : Popular Culture; LANGUAGE ARTS & DISCIPLINES : Linguistics : General; Soziolinguistik; Englisch; English language : Variation; English language : Social aspects; Soziolinguistik; Electronic books